Far from home: Bat activity and diversity in row crop agriculture decreases with distance to potential roost habitat - Louis Hunninck; Kjirsten Coleman; Melissa Boman; Joy O’Keefe (Global Ecology and Conservation, 2022)
As demand for food increases, agricultural production is poised to increase dramatically. Pesticides are commonly used to maintain high crop yield, though they have several drawbacks, including reduced efficacy over time and harmful effects to human and ecosystem health. Bats are highly effective predators of crop pests and have great potential to reduce crop damage resulting from insects. However, few studies have investigated how pest control by bats might change over large expanses of continuous row crop agriculture, which is common in the midwestern USA. Agricultural landscapes offer few roosting opportunities and could be difficult for bats to traverse, which might affect the degree of ecosystem services provided by bats. We hypothesized that with increasing distance into uninterrupted row crop agriculture 1) bat activity would decrease and 2) bat species richness would decrease, but that these effects would be buffered when insect pest abundance is high. We deployed 50 acoustic bat detectors over 10 transects in east-central Illinois from July to September 2021. In each transect, we placed detectors on crop field edges at increasing distance from a large riparian corridor assumed to be frequented by bats. Bat activity was high across the landscape but declined by 56% from the forest edge to 4000 m into row crop agriculture, while bat diversity decreased by 34%. Pest abundance seemed to decrease overall bat activity but had no effect on bat diversity. These results indicate that bats, although able to have a large effect on crop pest reduction, might not be as efficient in suppressing crop pests in vast uninterrupted agricultural landscapes which offer scant roost availability. Our work will inform recommendations to landowners and private lands managers on ways to increase bat access to roosts and forest cover near agricultural areas, thereby enhancing the potential for bats to provide pest control services.